2008
DOI: 10.1128/jb.00534-08
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the cbb 3 -Type Cytochrome Oxidase Requires Specific CcoQ-CcoP Interactions

Abstract: Cytochrome cbb 3 -type oxidases are members of the heme copper oxidase superfamily and are composed of four subunits. CcoN contains the heme b-Cu B binuclear center where oxygen is reduced, while CcoP and CcoO are membrane-bound c-type cytochromes thought to channel electrons from the donor cytochrome into the binuclear center. Like many other bacterial members of this superfamily, the cytochrome cbb 3 -type oxidase contains a fourth, non-cofactor-containing subunit, which is termed CcoQ. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 57 publications
1
58
0
Order By: Relevance
“…The fourth subunit of cytochrome oxidase cbb 3 , CcoQ, has been suggested to be an assembly factor required for the formation of a fully active cytochrome oxidase complex (38,39). However, unlike most other bacteria, the gonococcal cytochrome oxidase also transfers electrons to nitrite, and the nitrite and oxygen reduction functions are essentially independent (compare data in reference 24 with those in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The fourth subunit of cytochrome oxidase cbb 3 , CcoQ, has been suggested to be an assembly factor required for the formation of a fully active cytochrome oxidase complex (38,39). However, unlike most other bacteria, the gonococcal cytochrome oxidase also transfers electrons to nitrite, and the nitrite and oxygen reduction functions are essentially independent (compare data in reference 24 with those in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…CcoO and CcoP are transmembrane monoheme and diheme cytochromes c, respectively (5). CcoQ is known to affect the stability of the cbb 3 complex, but it is not necessarily a component of purified cbb 3 (6)(7)(8).…”
mentioning
confidence: 99%
“…In Bradyrhizobium japonicum and R. sphaeroides, it was shown that deletion of CcoQ had no effect on assembly or catalytic activity of cbb 3 -CcO (22,56). In contrast, the activity of R. capsulatus cbb 3 -CcO was significantly reduced in the absence of CcoQ (23). Additionally, it has been demonstrated that CcoQ is required to protect the R. sphaeroides cbb 3 -CcO from degradation under aerobic conditions (24).…”
Section: Figmentioning
confidence: 99%
“…It has also been suggested to serve as a gas-sensing element because one reduced heme c in this subunit can bind carbon monoxide (8). CcoQ is the smallest subunit present in some cbb 3 -CcOs, which was shown to be involved in the stabilization of the cbb 3 -CcO by interaction with subunit CcoP in Rhodobacter capsulatus (23) and by protection of the cbb 3 -CcO from oxidative destabilization in Rhodobacter sphaeroides (24).…”
mentioning
confidence: 99%